EDITORIAL - Ivan Čuk (University of Ljubljana Press (Založba Univerze v Ljubljani), 2021)
Dear friends, we are all waiting for OG to start in Tokyo. We expect the Games to be another step into the third milenium gymnastics. Nikita Nagorny with the triple salto backward piked on floor and Simone Biles with double piked Yurchenko on vault have already made such a step and on OG they will show it to the world audience. With the June issue, we have added a DOI number to each article, as our university and sports faculty are authorized to generate DOI. With the unique DOI number your articles will be more visible in various publishing apps. We strongly recommend all authors to use Grammarly or Instatext (you can find them through any search program on www) before sending the text to the editor. Both tools are free and can improve your text. The first article should support idea of »Mens sana in corpore sano«, but with the knowledge that a totalitarian regime has ordered it, shaded a bit. And again, authors from different countries have contributed their knowledge and we are proud that the knowledge is spread. Anton Gajdoš has prepared 21 short historical notes until today and introduced a short reminder on OG in Tokyo 1964. Two exceptional gymnastics friends passed away from February. Istvan Bercy from Hungary (he was judge at 8 Olympic Games) and Jože Senica from Slovenia (he was judge at Barcelona OG, and coached Miroslav Cerar few years) went among the stars. Our condolences to family and friends. Just to remind you, if you cite the journal, its abbreviation in the Web of Knowledge is SCI GYMN J. I wish you an enjoyable read and many ideas for new research projects and articles, Ivan Čuk Editor-in-Chief